Pengaruh Kepemimpinan Transformasional dan Pemberdayaan terhadap Motivasi Guru SD Negeri di Kecamatan Duren Sawit Jakarta Timur - Priyadi, Sarsito (Program Pascasarjana Universitas Ibrahimy, 2019)
The objective of this research is to obtain information about the effect of transformational leadership and empowerment on teachers achievement motivation. The research was conducted to all of elementary schools teachers at the district of Duren Sawit, East Jakarta by using a survey method with path analysis applied in testing hypothesis. The number 80 teachers as sample was selected by using Slovin formula. The research conclude: (1) There is a direct positive effect of transformational leadership on achievement motivation. (2) There is a direct positive effect of empowerment on achievement motivation. (3) There is a direct positive effect of transformational leadership on empowerment.